Supply chain development for the lean enterprise Interorganizational cost management. - Cooper, Robin, 1951-; Slagmulder, Regine (Strategies in confrontational cost management series, 1999)
"In this book, Cooper and Slagmulder use nine case studies to document how successful companies transfer cost management pressures across organizational boundaries. However, more than just cost management must cross interorganizational boundaries. Suppliers are also a major source of innovation for lean enterprises. Successful supplier networks encourage every firm in the network to innovate and compete more aggressively. Read this book to learn how to manage your supply chain to forge a competitive advantage while reducing costs."